The Effect of Consumption, Investment, and Government Expenditure on the Economic Growth of West Java Province - Erika Agustiani Sihotang; Asep Munir Hidayat; Billy Tejaarief; Kenedi Kenedi; Anti Wulan Agustini (Transpublika Publisher, 2025)
The trajectory of economic expansion in West Java is contingent upon three cardinal determinants: household consumption, capital investment, and fiscal expenditure. Consumption propels aggregate demand for commodities and services, investment augments productive capacity, while governmental disbursement, particularly directed toward infrastructural advancement and social initiatives, engenders employment prospects and elevates communal welfare. This paper seeks to scrutinize the ramifications of consumption, investment, and fiscal spending on the economic progression of West Java Province throughout the 2020–2024 interval. The investigation employs a Secondary Data Analysis (SDA) paradigm underpinned by a quantitative orientation. The empirical sample encompasses 27 regencies/municipalities within West Java Province, delineated through a saturated sampling modality. The collated data were subjected to panel data econometric techniques utilizing the EViews 12 platform. Findings shed light that consumption, investment, and governmental expenditure exert discernible influences upon economic growth, albeit with heterogeneous magnitudes across territorial units. In conclusion, these three variables manifest statistically significant bearings on West Java’s economic development, though the intensity of their effects diverges among regions.